Towards Fully Purposing Universities to Deliver Public Benefit - Tyndale, Nicholas; Chaytor, Sarah; Price, G. David (Frontiers in Sustainability, 2021)
In leadership positions at UCL, we have spent more than a decade seeking to fulfil our university’s founding commitment – inspired almost two centuries ago by the utilitarian philosopher Jeremy Bentham – to innovation, accessibility and relevance for the benefit of humanity. Our guiding principle has been to make our institution and its activities greater than the sum of its parts. To enable us to have most impact in “sustainable human progress”, we have focused our approach on cross-disciplinarity – by which we mean collaboration between experts in different disciplines that transcends subject boundaries – because the problems faced by society cannot be solved by research from one discipline alone. In recent years we have come to understand the boundaries between disciplines to be a subset of the many types of barriers – such as those between communities (disciplinary, academic and otherwise) and between different kinds of activity – that can inhibit the fulfilment of our vision to maximise our public benefit. In order to address crucial challenges – from the local to the global – we need to form collaborations across society that increase our mutual knowledge and engagement. We need to understand how the translation and application of knowledge will change in different settings and according to different practicalities. And we need to better reflect and enhance our role as convenors of different stakeholders to promote greater shared dialogue, co-creation and action.